2020
DOI: 10.3390/jcm9061973
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immune Microenvironment Clusters in Localized Prostate Adenocarcinoma: Prognostic Impact of Macrophage Enriched/Plasma Cell Non-Enriched Subtypes

Abstract: Background: Prostate cancer (PCa) is characterized by significant heterogeneity in its molecular, genomic, and immunologic characteristics. Methods: Whole transcriptome RNAseq data from The Cancer Genome Atlas of prostate adenocarcinomas (n = 492) was utilized. The immune microenvironment was characterized using the CIBERSORTX tool to identify immune cell type composition. Unsupervised hierarchical clustering was performed based on immune cell type content. Analyses of progression-free survival (PFS), distant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Our study found that TRIM8 was negatively correlated with resting mast cells. Similar studies have found that innate and adaptive immune response cells, such as resting mast cells, have extensive connections with the external environment, can release inflammatory mediators and other factors that affect tumor growth, and inhibit cancer progression 28 , 41 . These observations are consistent with those found in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Our study found that TRIM8 was negatively correlated with resting mast cells. Similar studies have found that innate and adaptive immune response cells, such as resting mast cells, have extensive connections with the external environment, can release inflammatory mediators and other factors that affect tumor growth, and inhibit cancer progression 28 , 41 . These observations are consistent with those found in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Ultimately, M0s may represent another type of TAM or an incompletely differentiated M2 [ 51 ]. M0 macrophages have been found to be one of the cell subsets most strongly associated with poor outcome in breast cancer [ 53 ], prostate cancer [ 54 ] and lung adenocarcinoma [ 55 ], whereas reduced M0 content has been associated with better prognosis in bladder cancer [ 56 ]. In a comprehensive analysis of digestive system cancers, M0 macrophages were among the most prevalent immune cell fractions, with M0-enriched clusters associated with decreased recurrence-free survival and worse prognostic immune score [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…may represent another type of TAM or an incompletely differentiated M2 [47]. M0 macrophages were found to be one of the cell subsets most strongly associated with poor outcome in breast cancer [49], prostate cancer [50], and lung adenocarcinoma [51], while reduced M0 content has been associated with better prognosis in bladder cancer [52]. In a comprehensive analysis Interleukin-10 is an immunosuppressive cytokine produced mainly by monocytes.…”
Section: Discussionmentioning
confidence: 99%